CLINICAL AND EPIDEMIOLOGICAL ASPECTS OF INTESTINAL INFECTIONS COUSED BY CONDITIONALLY PATHOGENIC FLORA - Matyakubova Feruza Egamovna (Web of Journals Publishing, 2024)
World health storage organization (WHO) information according to year the world across approx one to the billion near man diarrhea with gets sick It's sharp intestine infections (O'II) are high level all spread out contagious diseases between stable ranks 2-3 [3, 7] . Last in years sharp intestine of infections etiological It is known that the structure has also changed done bacterial infections share is increasing . This 87.6 percent of infections bacterial to nature have Most of them belong to the Enterobacteriaceae family incoming conditionally pathogenic from bacteria come comes out [1, 6]. The widest spread out pathogens including Proteus mirabilis, P. vulgaris, Klebsiella pneumoniae, Enterobacter cloacae, E. aerogenes, Citrobacter freundii and Serratia etc available [2, 4]. Conditionally pathogenic of microorganisms a person to health effect different environment factors and socio-economic conditions under the influence of their biological characteristics change with depend Intestine in the microflora changes , esp in children , immune to the system effect shows that while cellular and humorous of immunity to the violation take of the organism protection ability reduces [5]. As a result , such circumstances allergic , infectious and autoimmune diseases development reason will be
Keywords: opportunistic flora, acute intestine infection , bacterial infection.